Contextual Effect of Community Health Center on Patient Satisfaction of Health Care Service in Ngawi, East Java - Hendra Dwi Kurniawan; Didik Tamtomo; Bhisma Murti (Journal of Health Policy and Management, 2019)
Background: Perceived patient satisfaction is an important component of health care quality. This study aimed to determine the effect of age, education, income, health financing, quality of health care service, and the contextual effect of community health center on patient satisfaction. Subjects and Method: This was a cross-sectional study conducted in 25 community health centers in Ngawi, East Java, from October to November 2018. A sample of 200 patients was selected by stratified random sampling. The dependent variable was patient satisfaction. The independent variables were age, education, income, health insurance, and quality of health care service. The data were collected by questionnaire and analyzed by a multilevel logistic regression.Results: Age ≥35 years (b = 0.99; 95% CI= 0.17 to 1.81; p<0.019) and good quality of health care service (b= 1.68; 95% CI= 0.78 to 2.59; p<0.001) increased patient satisfaction. Education ≥senior high school (b= -1.59; 95% CI= -2.49 to -0.68; p<0.001), income ≥Rp 1,569,832 (b= -1.32; 95% CI= -2.25 to -038; p<0.006), and membership of national health insurance (b= -1.55; 95% CI= -2.47 to-0.63; p< 0.001) decreased patient satisfaction. Community health center had contextual effect on patient satisfaction with ICC= 13.03%.Conclusion: Age ≥35 years and a good quality of health care service increase patient satisfaction. Education ≥senior high school, high income, and membership in national health insurance decrease patient satisfaction. The community health center has a contextual effect on patient satisfaction.Keywords: patient satisfaction, community health center, multilevel analysisCorrespondence: Hendra Dwi Kurniawan. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: hendradeeka@gmail.comJournal of Health Policy and Management (2019), 4(1): 23-30https://doi.org/10.26911/thejhpm.2019.04.01.03